Molecular cloning and expression dynamics of Atrogin-1 in muscle tissue of Russian sturgeon (Acipenser gueldenstaedtii) under high salt stress - Yong-Juan Mo; Yi-Li Gao; Shi-Jjian Xu; Bin Wang; Jingping Wu; Peng Yu; Ming Li; Xiangtao Kang; Zhi-Qiang Han (Aquaculture Reports)
Atrogin-1, a muscle-specific ubiquitin ligase, is integral to the regulation of protein degradation and plays a pivotal role in the targeted degradation of critical muscle signaling proteins, which can lead to skeletal muscle dysfunction. High salt stress is known to induce muscle atrophy and alter the physical and chemical properties of muscle in cultured fish. Conversely, an optimal salinity level can enhance muscle quality. The Russian sturgeon (Acipenser gueldenstaedtii), an anadromous species of significant economic value, is potentially adaptable to brackish water environments, yet the underlying regulatory mechanisms remain elusive. To elucidate the regulatory mechanism of Atrogin-1 in response to high salt stress in Russian sturgeon, we conducted cDNA cloning and expression analysis. The cDNA encoding the Russian sturgeon protein Atrogin-1 was successfully cloned, comprising 1472 bp and encoding 353 amino acid residues (with an open reading frame of 1062 bp). Utilizing the sequence of Russian sturgeon atrogin-1, we designed novel primers and a specific anti-peptide antibody for our study, confirming that atrogin-1 is selectively expressed in skeletal muscle and heart tissues. The sturgeons were then allocated into four experimental groups for salt stress exposure; one control group was maintained in freshwater, while the others were subjected to salinities of 8 ‰, 16 ‰, and 24 ‰, respectively. Quantitative PCR (qPCR) and western blot analysis were employed to assess Atrogin-1 expression levels under high salt stress. A significant upregulation of atrogin-1 mRNA was observed at salinities of 16 ‰ and 24 ‰ compared to the control group. Similarly, protein expression levels of Atrogin-1 were markedly elevated under the same salinity conditions. Our findings indicate that the modulation of Atrogin-1 expression is a sensitive indicator of the response to high salt stress. This research is anticipated to inform aquaculture practices and shed light on the selection of germplasm resources for the development of salt-tolerant Russian sturgeon strains.